Distribution of Leprosy Patients with and without Plantaris Ulcers - Cita Rosita Sigit Prakoeswa; Sari, Vida Cahlia Novita; Prajitno, Subur (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Leprosy is a chronic infectious disease caused by obligate intracellular Mycobacterium leprae, impacting public health. Leprosy causes deformity, and disability can lead to ulcer disease. Nerve involvement is essential in the emergence of ulcers on the feet, including in neuropathic ulcers. Neuropathic ulcers can be found on the soles of the feet and are often called plantar ulcers. The slow healing process of the ulcer will cause the plantar ulcer to become chronic. Purpose: To evaluate the characteristics of leprosy patients with and without plantar ulcers at the Leprosy Division of Dermatology and Venereology Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, 2015-2019. Methods: A retrospective study were conducted by examining medical records for five years (2015-2019) at the Leprosy Division of Dermatology and Venereology Outpatient Clinic of Dr. Soetomo General Academic Hospital Surabaya. Results: A total of 511 patients met inclusion criteria. In leprosy patients without plantar ulcers group, the characteristics were male (68%), female (32%), aged 26-35 years (25.4%), paucibacillary (8.1%) and multibacillary (91.8%), patients without leprosy reactions (58%), and patients under treatment (49%). In leprosy patients with plantar ulcers group, the characteristics were male (64.3%), female (35.7%), aged 26-35 years (31%), multibacillary (92.9%), patients without leprosy reactions (61.9%), patients in the RFT category (76%), the ulcer duration group with highest prevalence rate 1-6 months (38.1%), and the most common location of plantar ulcers was on the forefoot (95.2%). Conclusion: Leprosy without plantar ulcers was more common than leprosy with plantar ulcers, mostly in male, dominated in the 26-35 years old for patients leprosy without plantar ulcers, type MB (multibacillary) was most history of leprosy type. Leprosy without reaction was common in leprosy patients with and without plantar ulcers. Patients without plantar ulcers majority was MDTL therapy, patients with plantar ulcers was common RFT (Release From Treatment).